VARIABILITAS GENETIK, HERITABILITAS, DAN KEMAJUAN GENETIK FREKUENSI STOMATA DAN KANDUNGAN KLOROFIL BEBERAPA GENOTIPE KEDELAI GENERASI F4 - Sa?diyah, Nyimas (JURNAL AGROTROPIKA, 2011)
Indonesia has been known as soybean importer since domestic production was only 40% of the total demand. Hence, to lower the dependency of soybean import, national production must be enhanced by various means such as improvement of soybean varieties better adapted with local agroclimate conditions. The success of the selection is supported by data of genetic vari-ability, heritability, and genetic progress. Research was conducted at agricultural field station of Faculty of Agriculture, University of Lampung from August to December 2007. Experiment was laid out in a random-ized block design. Plant materials were 13 lines of F4-soybean. Stomatal frequency and leaf greenness were measured at leaves in R4 stage. Results were (1) the character of stomatal frequency showed a widespread genetic and phenotypic variability, high value of heritability, and medium genetic progress. (2) the character of leaf greenness measured with Minolta SPAD-502 showed a narrow genetic variability, widespread phenotypic variability, medium value of heritability, and low genetic progress. (3) the character of seed weight showed a widespread genetic and phenotypic variability, high heritability, and high genetic progress.